Empowered Women: Strategies to Increase Competitiveness in the Era of Society 5.0 through Entrepreneurship - Muhammad Bangun Siregar; Ritha F Dalimunthe; Endang Sulistya Rini; Yeni Absah (Randwick International of Social Science Journal, 2024)
This research aims to increase the competitiveness of women entrepreneurs in Medan City and Deli Serdang Regency, North Sumatra, through human resource transformation. In the Society 5.0 era, women have a crucial role in increasing competitiveness through entrepreneurship. Even though the business potential in the region is significant, human resources have not been fully optimized. This research identified several problems, including the low competitiveness of female entrepreneurs, lack of managerial experience, lack of innovation ability, and limited education. This research was conducted using a qualitative descriptive approach, involving 115 female entrepreneurs as respondents. The results of the analysis show that the majority of female entrepreneurs are aged 41-50 years, have 2-5 years of business experience, and most do not have a business license. Nevertheless, the quality of women entrepreneurs is considered good, especially in terms of interpersonal skills and responsibility for business. The analysis also reveals the importance of the quality of human resources in increasing competitive advantage. Technical skills, management, entrepreneurship and personal maturity were identified as key factors that need to be improved. It is hoped that the transformation of human resources can improve the quality and innovation of women entrepreneurs. In the context of digitalization, women entrepreneurs need to utilize digital marketing to expand business networks. As many as 46.09% of respondents agreed with this effort. Improving the quality of human resources in terms of mastery of information technology is crucial for taking advantage of digitalization opportunities. The results of the Forum Group Discussion emphasize the importance of the business community, in-depth training, and the role of the family in supporting women entrepreneurs. Technological innovation, understanding regulations, and halal certification are also considered important to improve product quality. This research contributes by identifying the problems and opportunities faced by women entrepreneurs in North Sumatra. By implementing the Social Entrepreneur Strengthening Model, it is hoped that the transformation of human resources can increase the competitiveness and welfare of women entrepreneurs and support local economic growth.